Wie man soziale Innovationen in strukturschwachen ländlichen Räumen befördern kann; How Social Innovation can be Supported in Structurally Weak Rural Regions - Gabriela B. Christmann (Leibniz-Institut für Raumbezogene Sozialforschung (IRS), 2020)
In vielen strukturschwachen ländlichen Regionen Europas hat sich in den vergangenen Jahrzehnten eine Abwärtsspirale in Gang gesetzt. Zwar sind die konkreten wirtschaftlichen und sozialen Bedingungen in den einzelnen Regionen Europas oft sehr unterschiedlich, dennoch zeigt sich tendenziell dasselbe Muster: Im Vergleich zu Städten sind die Bedingungen für das alltägliche Leben in strukturschwachen ländlichen Gebieten aufgrund einer geringeren wirtschaftlichen Produktivität, geringer Berufsperspektiven und einer sich verschlechternden infrastrukturellen Ausstattung (z.B. in der Daseinsvorsorge) eher ungünstig. Dies hat dazu geführt, dass immer mehr Landbewohnerinnen und -bewohner in die Städte abwanderten. Insbesondere jüngere, gut ausgebildete Personen haben ländlichen Regionen den Rücken gekehrt. Eine Folge davon ist, dass die dort benötigten Arbeits- bzw. Fachkräfte fehlen und sich die wirtschaftlichen Chancen der Regionen weiter verschlechtern. Dies macht es oft schwer, die Abwärtsspirale zu durchbrechen bzw. umzukehren. – – In fact, throughout Europe there is an abundance of innovative initiatives to be seen in the countryside (Olmedo/van Twuijver/O'Shaughnessy 2019), advanced by rural inhabitants, social entrepreneurs, or both in collaboration, and which is here termed "social innovation". To social innovation one can ascribe the potential for meeting the diverse challenges of our society. For some time, political decision makers have also placed hope in social innovation. Early on, the European Commission set itself the target of promoting the empowerment of people and the development of social innovation (Bureau of European Policy Advisers 2010; see also Jenson/Harrison 2013, Christmann 2020). There are, however, still many questions about the conditions in which social innovation emerges in rural areas, how its potential can be developed, and what support strategies can be used to assist it. The basis of this Policy Paper is empirical research that tackles these questions. By analysing innovative initiatives in the countryside, the conditions and the actor constellations necessary for their emergence has been reconstructed. The phases through which the processes of innovation are carried out have also been investigated, and critical junctures that could pose a threat to their further progress have been identified, as well as favourable factors. Using the example of failed initiatives, it has been possible to explore what conditions could be adverse, or what obstacles are insurmountable, for an innovative initiative.
Keywords: 710